SUBSCRIBERS’ ATTITUDE TOWARDS MOBILE COMMUNICATION SERVICE PROBLEMS IN TUTICORIN DISTRICT - Golden S, Anthony Rahul (International Journal of Research -GRANTHAALAYAH, 2016)
Increasing competition in mobile service sector has led the providers to realizing the need to focus on decrease the service problems to avoid the switching over to the competitors. Consumers play an important role in choosing a mobile service provider. This paper presents impact of service problems on subscribers’ satisfaction in Tuticorin Dist.